1995
DOI: 10.1021/bi00004a002
|View full text |Cite
|
Sign up to set email alerts
|

Specific DNA Recognition by EcoRV Restriction Endonuclease Induced by Calcium Ions

Abstract: In the presence of Mg2+, the EcoRV restriction endonuclease cleaves DNA specifically at its recognition sequence, but in the absence of divalent metal ions, it binds DNA without any specificity: gel-shift experiments had revealed multiple EcoRV-DNA complexes, due to the binding of one, two, three, or more molecules of protein per molecule of DNA, with the same equilibrium constant for each association. In this study, the binding of EcoRV to DNA was measured by gel shift in the presence of Ca2+, an ion that per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 25 publications
9
136
0
Order By: Relevance
“…The decline in processivity thus can be assigned to the effect of salt on weakening nonspecific binding. The affinities and the salt dependency of nonspecific DNA binding by BbvCI are comparable with other restriction enzymes (34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The decline in processivity thus can be assigned to the effect of salt on weakening nonspecific binding. The affinities and the salt dependency of nonspecific DNA binding by BbvCI are comparable with other restriction enzymes (34)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 54%
“…The key factor in determining the mean path length for 1D diffusion by a protein on DNA is its affinity for nonspecific DNA (8)(9)(10)(11). In this respect, BbvCI is comparable with other restriction enzymes (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…However, Ca 2ϩ , which does not promote DNA hydrolysis, has been extensively used as a Mg 2ϩ surrogate. With orthodox type II restriction endonucleases, Ca 2ϩ is commonly observed to increase the affinity for cognate DNA sequences often by considerable factors of up to 10 4 (35)(36)(37)(38)(39)(40). Recently it has been shown that the production of dimeric FokI complexes requires the presence of a divalent metal ion.…”
Section: Discussionmentioning
confidence: 99%
“…with R.EcoRV (35,36), R.MunI (37), R.PvuII (38), R.Cfr10I (39), and R.BamHI (40). Recently, Ca 2ϩ has been found to be essential for the formation of (FokI) 2 -(DNA) 2 complexes (12).…”
Section: Fig 2 Interaction Of the Mboii Restriction Endonuclease Wimentioning
confidence: 99%
“…Similar to EcoRV, a stable complex was formed in the presence of 10 mM Ca 2ϩ , although the activity of PvuII using Ca 2ϩ as a cofactor was negligible ( Fig. 2 and data not shown) (41). Several attempts to visualize specific PvuII-DNA complexes in the absence of divalent ions were attempted unsuccessfully (data not shown).…”
Section: Analysis Of Interaction Between Pvuii and Its Specific Bindimentioning
confidence: 93%